591. THE ROLE OF INTRAOPERATIVE HYPERSPECTRAL IMAGING (HSI) IN THE CASE OF USING COLON INTERPOSITION AFTER OESOPHAGECTOMY. (24th September 2022) - Zimmermann, Anne; Köhler, Hannes; Gockel, Ines; Moulla, Yusef
Abstract: Colon conduit is an alternative option for the reconstruction after oesophagectomy. The impact of using Hypersepctral Imaging (HSI) has been already proved in evaluating the perfusion of gastric conduit, but not in the case of using colon conduit. This is the first study described a new tool evaluating the perfusion of colon conduit and allowing us as esophageal surgeons to choose the appropriate side (left or right) of colon conduit and anastomosis site intraoperatively In 10 patients, who underwent reconstruction with a long segment colon conduit after oesephagectomy from 01.01.2018 till 01.04.2022. HSI was recorded in 8 of these patients at the root and tip of colon conduit after clamping the colic middle vessels allowing us to evaluate the perfusion and the appropriate side of colon conduit (Figure 1) Anastomosis Leakage (AL) grad I° was detected only in one patient (12.5%) of all included patients (n=8). There was no conduit necrosis in all of these patients. Re-anastomosis was necessary only in one patient. There were no need to conduit resection and esophageal diversion or to stent placement in all of included patients. Furthermore, there were no change of the selected side of colon conduit intraoperatively HSI is a promising novel intraoperative imaging tool to evaluate the perfusion of colon conduit objectively, which helping us to make the right decision regarding the side of the colon conduit as well as the site of the anastomosis intraoperatively.